Effects of single and combined applications of three root exudates of Sedum plumbizincicola on the phytoremediation efficiency of paddy soil contaminated with Cd - Xing, Qianwen; Cao, Xueying; Tan, Changyin; Sun, Lijuan; Deng, Yueqiang; Yang, Jia; Tu, Chen (Frontiers in Environmental Science, 2023)
Root exudates are carriers for the transfer of material, energy and information between plant roots and soils. Plants encountering environmental stresses such as heavy metal pollution adapt to the environment by producing and secreting root exudates. In this study, laboratory soil culture experiment and pot experiment with Sedum plumbizincicola were used to study the effects of single and combined application of three root exudates, citric acid, glycine, and fructose, on the Cd-activation and phytoremediation of Cd-contaminated paddy soil. Results from the soil culture experiment showed that for the single application of root exudates, all three root exudates significantly activated the Cd in soil as presented by the increased content of diethylenetriamine pentaacetic acid extracted Cd (DTPA-Cd). In Particular, citric acid (SC) at a relatively low concentration (2 mmol/kg) exhibited the best Cd activation efficiency by increasing DTPA-Cd in the soil by 66.12%. For the combined application of root exudates, citric acid in combination with glycine (SC + G, 1:3) had the best activation effect on the Cd in the soil. In the phytoremediation pot experiment, both the single application of citric acid at a low concentrate (1 mmol/kg) and the combined application of citric acid and glycine (1:1) significantly reduced the total Cd and DTPA-Cd in the soil and increased the biomass and the content of Cd in S. plumbizincicola; thus, the phytoremediation efficiency of Cd-contaminated soil increased by 42.33% and 35.61%. The results from this study suggest that citric acid plays a crucial role in Cd activation and phytoremediation with single or combined applications with glycine. However, the mechanisms under the synergetic interaction between citric acid and glycine require further investigation.